Exploring the impact of plant genotype and fungicide treatment on endophytic communities in tomato stems - Liu-Xu, Luisa; Ma, Liang; Farvardin, Atefeh; García-Agustín, Pilar; Llorens, Eugenio (Frontiers in Microbiology, 2024)
This study examines how plant genotype can influence the microbiome by comparing six tomato genotypes (Solanum lycopersicum) based on their traditional versus commercial backgrounds. Using Illumina-based sequencing of the V6-V8 regions of 16S and ITS2 rRNA genes, we analyzed and compared the endophytic bacterial and fungal communities in stems to understand how microbiota can differ and be altered in plant genotypes and the relation to human manipulation. Our results reflect that traditional genotypes harbor significantly more exclusive microbial taxa and a broader phylogenetic background than the commercial ones. Traditional genotypes were significantly richer in Eurotiomycetes and Sordariomycetes fungi, while Lasiosphaeriaceae was more prevalent in commercial genotypes. TH-30 exhibited the highest bacterial abundance, significantly more than commercial genotypes, particularly in Actinomycetia, Bacteroidia, and Gammaproteobacteria. Additionally, traditional genotypes had higher bacterial diversity, notably in orders like Cytophagales, Xanthomonadales and Burkholderiales. Moreover, we performed an evaluation of the impact of a systemic fungicide (tebuconazole-dichlofluanide) to simulate a common agronomic practice and determined that a single fungicide treatment altered the stem endophytic microbiota. Control plants had a higher prevalence of fungal orders Pleosporales, Helotiales, and Glomerellales, while treated plants were dominated by Sordariomycetes and Laboulbeniomycetes. Fungal community diversity significantly decreased, but no significant impact was observed on bacterial diversity. Our study provides evidence that the background of the tomato variety impacts the fungal and bacterial stem endophytes. Furthermore, these findings suggest the potential benefits of using of traditional genotypes as a source of novel beneficial microbiota that may prove highly valuable in unpredicted challenges and the advancement in sustainable agriculture.